SimPower-based analysis and design of a hybrid wind–diesel-superconducting magnetic energy storage system for simultaneous frequency and voltage control. Issue 6 (December 2019) - Abass, Aaqib Ali; Mufti, Mairaj Ud-Din
Power quality control in a stand-alone power system is a demanding task. For satisfactory operation, such systems are being augmented with fast-acting energy storage devices. In this article, a stand-alone wind–diesel system augmented with a small-rating superconducting magnetic energy storage system is considered for both reactive and real power balance. Suitable controllers are proposed which force the superconducting magnetic energy storage system to exchange both reactive and real power with the system under various perturbations. A simulation platform is developed in SimPower to virtually validate the system model and control design aspects. Superconducting magnetic energy storage system and its power electronic interface are represented by average value models and the various controller parameters are tuned using Genetic Algorithm. Simulation results show that both voltage and frequency of the system are improved.